Excited‐State Intramolecular Proton Transfer (ESIPT) for Optical Sensing in Solid State - Chen, Ling; Fu, Peng‐Yan; Wang, Hai‐Ping; Pan, Mei (Advanced optical materials, 2021)
Excited‐state intramolecular proton transfer (ESIPT) process brings about ultrafast keto‐enol tautomerism, which simultaneously induces the unique four‐leveled energy state cycle and concomitant multi‐emissions. Such transformation is easily affected by the environmental conditions, leading to intricate spectral responses. In contrast with the widely reported researches that inclined to the solution systems dissolved with ESIPT molecules, ESIPT materials including small organic molecules, metal‐organic materials, covalent‐organic frameworks, and so on, which can be formed in solid state are emerging in recent years, bringing more scientific information and novel applications for the family of ESIPT materials. In this short review, the progress for the different types of these materials will be introduced, especially their optical sensing performances and mechanisms, like responses to external physical stimulations (pressure, temperature, light), solvent polarities, pH, ions, and small molecule compounds. And the potential photophysical and photochemical applications will also be surveyed. In this review, a summary introduction of ESIPT (excited state intramolecular proton transfer) materials in the solid state including small organic molecules, metal‐organic frameworks, and covalent‐organic frameworks is given. The four‐leveled energy state cycle based keto‐enol emissions of these materials respond to temperature, pressure, solvent, ions, light, and so on, and can be applied widely in optical sensing fields.